A COST VARIATION COMPARISON AMONG ORAL ANTI-MIGRAINE DRUGS AVAILABLE IN THE INDIAN MARKET - MISHRA, AKASH; MISHRA, POOJA SOLANKI; KUSHWAH, ANJALI; GUPTA, KAMAYANI (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: Our study aimed to evaluate the cost percent variation and cost ratio of different brands of oral anti-migraine drugs available in Indian market. Methods: The cost of various commonly used oral anti-migraine drugs were taken from the latest issue of Current Index of Medical Specialities January 2022, Drug Today January-April 2022 and 1 mg online site. Cost percent variation and Cost ratio were calculated. Results: A total of 7 single anti-migraine drugs and 9 Fixed-Dose Combinations (FDCs) showed a wide range of cost variation. The highest cost percent variation of 433% was seen in Sumatriptan 50 mg with a cost ratio of 5.33, whereas Amitriptyline 10 mg showed the lowest cost percent variation of 47.9% with a cost ratio of 1.47. Among FDCs Naproxen 500 mg+Sumatriptan 85 mg showed the highest cost per cent variation of 400% with a cost ratio of 5.25 and Propranolol 40 mg+Flunarizine 10 mg showed the lowest cost per cent variation of 46.56% with a cost ratio of 1.46. Conclusion: Our study showed a wide variation in the cost of oral anti-migraine drugs available in the Indian market, which provides insight to the healthcare professional and gives Drug Price Control Order (DPCO) authorities to minimize the financial burden and improve patient compliance.